Ageing and inequality: unintentional death in the elderly in Campinas in the 21st century. (30th September 2020) - Komoda, D S; Geronimo, C; Bravo, M; Cordeiro, R C; Ruiz, A M P
Abstract: According to WHO falls are the second leading cause of preventable unintentional death and people older than 65 years of age are more likely to suffer from fatal falls. Low and middle-income countries are most affected with 80% of fall related deaths. This study provides an overall view of fall-related deaths in the city of Campinas, Brazil, with special attention to the elderly in the last 2 decades. This study aims to highlight the unequal distribution of deaths related to fall, concerning the elderly in Campinas (total population of around 1, 000, 000), which in 2010 had a very high Human Develop Index (0.805), but also a very high inequality rate (Gini index of 0.56 in 2010). This ecological study in Campinas evaluates fall-related deaths in the elderly between years 2000 and 2018. Trend analysis were applied to the specific mortality ratios related to falls obtained from Brazil's official databases. Specific mortality trends were also analyzed regarding Human Development Index by neighborhood. The number of deaths due to fall in the elderly throughout the period totaled 1700 (1 million of population). The annual average was 85 (minimum of 31 in 2000 and maximum of 157 in 2018). Although trend analysis of mortality in the elder due to "overall external causes" and of mortality due to "fall in the elderly" didn't show clear growing tendencies (R2=0.546 and R2=0.622), the ratio between "number of deaths due to fall in the elderly" and "total deaths due to fall" shows a reliable average of 1.17% increase per year (from 3.73% in 2000 to 26.03% in 2018, R2=0.93). Trend-analysis based on community HDI mortality rates additionally shows a tendency of increase both in "number of deaths" and "mortality rate" in low-HDI elder (with R2=0.85 and R2=0.786). Despite decreasing violence levels in Campinas, fatal deaths due to fall seem to target low-HDI elder population. Effort must be taken in all levels of the healthcare system as well as in policies to soften inequality's effect. Key messages: Violent, unintentional causes of death in the elderly population are increasing along with population ageing. Politicians and health managers must pay attention to inequality-related health problems and take into account population ageing for a sustainable universal health system coverage.